Robert D. Hill, Seven Strategies for Positive Aging, W.W. Norton & Company, New York-London 2009, ss. 163 - Konieczna-Woźniak, Renata (Wydawnictwo Naukowe UAM, 2013)
Recenzja książki Roberta D. Hill'a pt."Seven Strategies for Positive Agin"